What Determines Consumer Financial Distress? Place- and Person-Based Factors. (5th May 2022) - Keys, Benjamin J; Mahoney, Neale; Yang, Hanbin
Abstract: We use credit report data to study consumer financial distress in America. We report large, persistent disparities in financial distress across regions. To understand these patterns, we conduct a "movers" analysis. For collections and default, there is only weak convergence following a move, suggesting these types of distress are not primarily caused by place-based factors (e.g., local economic conditions and state laws) but instead reflect person-based characteristics (e.g., financial literacy and risk preferences). In contrast, for personal bankruptcy, we find a sizable place-based effect, which is consistent with anecdotal evidence on how local legal factors influence personal bankruptcy. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.